EFEKTIVITAS PEMUNGUTAN PAJAK PARKIR DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KARAWANG TAHUN 2019-2022 (Studi Kasus Mall di Kabupaten Karawang): (Studi Kasus Pusat Perbelanjaan Di Kabupaten Karawang) - Muhammad Saepulloh; -, Yanti (Politeknik Negeri Jakarta, 2023)
Regional original income comes from the collection of taxes and fees in each region. Parking tax is one of the biggest contributors when compared to other sources of income. Pariking tax has a significant role in region income so that it can optimally increase region develpoment and the economy. This study aims to determine the effectiveness of parking tax collection and to analyze the contribution of parking tax as a source of local revenue in Karawang regency. This research methodology is quantitative and uses an associative approach. The findings of the simultaneous test with the F test show that the effectiveness of taxes and the collection of parking taxes have a large impact on local revenue with a value of 619.196. Parking tax contribution variable with a value of 3.079 own significant influence on local original income according to the findings of partial testing, as well as the effectiveness of parking taxes has a sizeable influence of 6.185 on regional original income of Karawang Regency. In 2021 parking tax revenue will have a ratio of 105.45% and will increase by 0.07% to 105.52% in 2022.